EFFECT OF VITAMIN E (α TOCOPHEROL) ADMINISTRATION ON APOPTOSIS OF GERMINAL CELLS EPITHELIUM TESTIS IN SPRAGUE DAWLEY WHITE STRAIN RATS AFTER EXPOSED BY CISPLATIN - Nugroho, Achmad; Djatisoesanto, Wahjoe; Soebadi, Doddy M (Indonesian Journal of Urology, 2019)
Objective: To determine the differences of germinal epithelial testicular cell apoptosis in white Sprague Dawley strain rat that received combination of cisplatin and vitamin E compared to Sprague Dawley strain rat that received cisplatin only. Material & Methods:  Twenty four Sprague Dawley rats were divided into 4 groups randomly. Group 1 Negative Control (NC) was given an injection of 1 cc 0.9% normal saline intraperitoneally as a placebo, group 2 Positive Control (PC) was given 5 mg/kgBW cisplatin intraperitoneally, group 3 (P1) was given cisplatin injection 5 mg/kgBW intraperitoneally + vitamin E (α tocopherol) 50 mg/kgBW by gavage and group 4 (P2) was given cisplatin injection 5 mg/kgBW intraperitoneally + vitamin E (α tocopherol) 200 mg/kgBW by gavage. Vitamin E (α tocopherol) was given 3 weeks before up to 4 weeks after cisplatin injection. Observation of the germinal epithelial cells apoptosis was carried out by calculating germinal epithelial cells apoptosis in the cross-section preparations of the seminiferous tubule which gave a positive reaction to the apoptag staining, using a 400x magnification light microscope. Results: Apoptosis on positive control (PC) group was different significantly compared to the negative control (NC) group (p<0.05). There was a significant difference in the apoptosis of germinal epithelial testicular cells in the cisplatin + vitamin E 50 mg/kgBW compared to the PC group (p<0.05). The cisplatin + vitamin E 200 mg/kgBW group; had a lower number of apoptosis compared to the cisplatin + vitamin E 50 mg/kgBW (p<0.05). Conclusion: Vitamin E provides a protective effect on decreasing the amount of apoptosis due to cisplatin exposure. The protective effect of vitamin E is dose-dependent.